DESAIN MASKOT DAN PROMOSI PARIWISATA KOTA MUARA TEWEH KALIMANTAN TENGAH - Rintania Rosita Citra Dewi; Handriyotopo Handriyotopo (Pendhapa, 2019)
Promotion is an important tool for the development of the tourism industry which is being promoted by the government. Likewise for the city of Muara Teweh in Central Kalimantan Province, which is developing the tourism economic sector. Promotional activities are important so that the potential for superior and unique tourist destinations can be an alternative for tourists to visit the province of Central Kalimantan. The design of tourism promotion in Muara Teweh city with a visual approach using mascot as a promotional strategy through the concept of visual identity has a different persuasive appeal to the promotion approach that has been done before. The mascot creation method begins with qualitative research with field observations through the design stages of design principles namely sketches, tumbnails, experimentation, and design executions that incorporate visual elements from endangered Kalimantan animal figures, namely Orangutans, Honey Bears, and Hornbills. The combination of these three animal element figures became the city mascot of Muara Teweh named "Arai" which means happy (spirit). Thus "Masai Arai" is expected to be able to represent the visual identity of the promotion of the city of Mura Teweh, Central Kalimantan, to support the communication process of message promotion through above-line advertising media and below-line media as well as merchandise.Keywords: Promotion, Mascot, Muara Teweh Tourism